The Effect of Exchange Rate and Money Supply on Consumer Price Index of Laos - Duangdara, Chanthanome; Siphanthong, Bounthavy; Sengdala, Chansamone; Sioudomphan, Soutthavone (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This research aims to 1) the effect of the exchange rate and the money supply on the consumer price index of the Laos in the long run and 2) the effect of the exchange rate and the money supply on the consumer price index of the Laos in the short run. The data used are the information on the kip/US dollar exchange rate, the money supply, and the consumer price index, which are all quantitative data obtained from the quarterly statistics of the Bank of the Laos, by analyzing the data to obtain the parameters of the linear regression equation with the long-term relationship model (Co-integration) using the Johansen and Juselius method and analyzing the short-term equilibrium relationship (ECM) of the impact of the exchange rate and the money supply on the consumer price index of the Laos through the E-view 10 program. The results of the research found: 1) the impact of the exchange rate and the money supply on the consumer price index of the Laos in the long run found that, the exchange rate fluctuations and the changes in the money supply can explain the consumer price index determined in the long run by 93.40%. Also, the exchange rate (Exc) of kip/US dollar has the most positive impact by 143.46%. 2) The impact of the exchange rate and the money supply on the consumer price index of the Laos in the short run found that, the exchange rate fluctuations and the changes in the money supply can explain only 58.25% of the consumer price index determined in the short run. It is also found that the changes in the money supply (M2) have the most positive impact on the consumer price index of the Laos by 95.44%.